To Choose or Not to Choose: Establishing a Correlation Between Choice, Collaboration, and Classroom Engagement - Krisandra Johnson (Networks: An Online Journal for Teacher Research, 2024)
Not all 8th-grade students have an outspoken passion for reading; however, most of them do like choices. This action research study establishes a correlation between offering choices in the English Language Arts classroom and increased affective, behavioral, and cognitive engagement. The participants for this research were an 8th-grade class at a Midwest, urban public school. Providing students with reading choices, assignment options, opportunities to collaborate with peers, and multiple assessment forms to choose from demonstrated an increase of not only effective engagement but also cognitive and behavioral. From observations and student data, collaboration, the researcher determines that collaboration is a crucial aspect of student engagement.
Keywords: Student choice; classroom engagement; collaboration; middle-school reading; classroom choices; Classroom Engagement Inventory